Climatic Impact of Volcanic Eruptions - Gregory A. Zielinski (The Scientific World Journal)
Volcanic eruptions have the potential to force global climate, provided they are explosive enough to emit at least 1–5 megaton of sulfur gases into the stratosphere. The sulfuric acid produced during oxidation of these gases will both absorb and reflect incoming solar radiation, thus warming the stratosphere and cooling the Earth’s surface. Maximum global cooling on the order of 0.2–0.3°C, using instrumental temperature records, occurs in the first 2 years after the eruption, with lesser cooling possibly up to the 4th year. Equatorial eruptions are able to affect global climate, whereas mid- to high-latitude events will impact the hemisphere of origin. However, regional responses may differ, including the possibility of winter warming following certain eruptions. Also, El Niño warming may override the cooling induced by volcanic activity. Evaluation of different style eruptions as well as of multiple eruptions closely spaced in time beyond the instrumental record is attained through the analysis of ice-core, tree-ring, and geologic records. Using these data in conjunction with climate proxy data indicates that multiple eruptions may force climate on decadal time scales, as appears to have occurred during the Little Ice Age (i.e., roughly AD 1400s–1800s). The Toba mega-eruption of ~75,000 years ago may have injected extremely large amounts of material into the stratosphere that remained aloft for up to about 7 years. This scenario could lead to the initiation of feedback mechanisms within the climate system, such as cooling of sea-surface temperatures. These interacting mechanisms following a mega-eruption may cool climate on centennial time scales.